(untitled) (Research, Society and Development, 2021)
The study proposed here is about a bibliographic review where several literature related to the proposed theme were consulted. And in articles published on the internet that allowed the work to take shape and to be based on, aiming to clarify Education professionals on the aforementioned theme from the position of several authors in the area, such as: Baremblitt (1996); Lourau (1996); Ulloa (2012); Bourdieu (1977); Castoriadis (1965) among others, considered scholars who sought to understand and research in a deeper way in order to clarify the issue at hand. Then, through the studies carried out here and the conclusions evidenced, it is possible to acquire subsidies for more consistent and in-depth discussions on this theme in the educational area.